MODIFIED CLEFT LIP EVALUATION PROFILE (MCLEP) INDEX FOR UNILATERAL CLEFT LIP REPAIR OUTCOME ASSESSMENT IN SURABAYA CLP CENTER - Robertus Arian Datusanantyo; Hutagalung, Magda Rosalina; Rizaliyana, Sitti (Universitas Airlangga, 2020)
Highlights: The study revealed that there were no notable variations in the ultimate scores, regardless of whether the cleft lip was complete or an alveolar cleft was present. If the palate cleft was not present, unilateral cleft lip repair yielded considerably superior results, showing enhancements in both total lip and nose scores. Abstract: Introduction: Cleft lip and/or palate is the most common craniofacial congenital anomaly encountered by the plastic surgeon. Both reconstruction and outcome assessment are challenging. This study aimed to assess the outcome of unilateral cleft lip repair in the Surabaya CLP Center. Methods: All patients who underwent unilateral cleft lip repair in 2017 were included in the study. Those without complete photographs at minimally 52 weeks after surgery were excluded. The photographs of patients taken at least one-year post-surgery were assessed using a modified cleft lip evaluation profile (MCLEP) index. The data were then analyzed using statistical software. Results: There were 38 subjects included in the study. There was no significant difference in the final scores obtained based on completeness of the cleft lip and the presence of alveolar cleft. The total nose score was significantly better in the left side cleft (p = 0.002). When palate cleft was absent, the total lip score (p= 0.038), the total nose score (p = 0.008), and total score (p = 0.000) were also significantly better. Conclusion: The unilateral cleft lip repair in CLP Center Surabaya yielded good and symmetrically acceptable results. The study failed to observe the different outcomes of unilateral cleft lip repair based on completeness of the cleft lip and the presence of alveolar cleft. However, the unilateral cleft lip repair outcome was significantly better in the absence of palate cleft.